PENGARUH VARIASI JENIS ABU BOILER DAN KOSENTRASI HCl TERHADAP SIFAT FISIS SILIKA GEL HASIL SINTESIS - Meidinariasty, Anerasari; Purnamasari, Indah; Zamhari, Mustain; ., Fadarina; Permadi, Jekasyah; Fadillah, Nadia Zaky; Luthfiah, Sakinah (Politeknik Negeri Sriwijaya, 2020)
Efforts to minimize environmental pollution caused by solid waste in the form of boiler ash are managed and reused into new materials that have economic value. Boiler ash has a high enough silica content which can be used as an alternative raw material for making adsorbents in the form of silica gel. This study aims to synthesize silica gel from variations of boiler ash and determine the effect of HCl concentration on its physical properties. The boiler ash used comes from PT Tanjungenim Lestari Pulp and Paper, PT Pupuk Sriwidjaja and PT Sriwijaya Palm Oil Indonesia. Silica gel synthesis was carried out by extracting boiler ash with 3 M NaOH solution for 1 hour, then the extraction results in the form of Sodium Silicate were precipitated using HCl with various concentrations of 1, 3 and 5 M. The physical properties of the synthesized silica gel were analyzed by analyzing the SiO2 content, water content, and absorption capacity of water vapor. The effect of HCl concentration on the physical properties of the synthesized silica gel showed the highest yield value in SG PP, SG PS, and SG PO respectively amounted to 15.6176%, 21.6115% and 24.5215%.The highest SiO2 content value in a row in SG PP, PS SG and SG PO amounted to 39.48%, 52.73% and 50.74%.